Global nutrition report 2014: Actions and accountability to accelerate the world's progress on nutrition - International Food Policy Research Institute (International Food Policy Research Institute, 2014)
The Global Nutrition Report (GNR) provides a global profile and country profiles on nutrition for each of the United Nations’ 193 member states, and includes specific progress for each country. It will be a centerpiece of the Second International Conference on Nutrition (ICN2) in Rome on 19-21 November, organized by the UN Food and Agriculture Organization and the World Health Organization.